2012
DOI: 10.1080/10934529.2012.646099
|View full text |Cite
|
Sign up to set email alerts
|

Levels and distribution of synthetic musks and polycyclic aromatic hydrocarbons in sludge collected from Guangdong Province

Abstract: The levels and distribution of six polycyclic musks, three nitromusks and 15 polycyclic aromatic hydrocarbons (PAHs) were investigated in sludge collected from 19 municipal wastewater treatment plants (WWTPs) in six cities in Guangdong Province, China. PAHs were detected in all of the sludge samples, and the levels of the total 15 PAHs ranged from 177.2-4421.8 µg/kg dry weight (dw). Four polycyclic musks, 4-acetyl-1,1-dimethyl-6-tert-butylindan (ADBI), 6-acetyl-1,1,2,3,3,5-hexamethylindan (AHMI), 1,3,4,6,7,8-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…The detailed analytical parameters have been reported previously [16,17]. Â 0.25-mm film; Thermo Fisher Scientific), with helium as the carrier gas at a flow rate of 1 mL/min.…”
Section: Sample Analysesmentioning
confidence: 99%
“…The detailed analytical parameters have been reported previously [16,17]. Â 0.25-mm film; Thermo Fisher Scientific), with helium as the carrier gas at a flow rate of 1 mL/min.…”
Section: Sample Analysesmentioning
confidence: 99%
“…However, the F2 sample, which originated from a domestic wastewater treatment plant in Fosan City, contained the highest concentrations of ∑ all PBDEs (5,052 ng/g) and BDE-209 (5,010 ng/g). Zeng et al (2012) found that the highest concentrations of PAHs (4,422 ng/g) were also detected in this sample (F2). The responsible WWTP received 90 % of its input from domestic sewage and an additional 10 % from industrial wastewater from ceramic and stainless steel factories.…”
Section: Concentrations In the Sludge Samplesmentioning
confidence: 60%
“…Although PAHs in sewage sludge F5 were quite high (3,294 ng/g), its PBDEs were low (1,297 ng/g). This observation may be related to the fact that this sludge sample was primarily originated from treatment of petroleum-related wastewaters (Zeng et al 2012). When the concentrations of PBDEs in this investigation were correlated with those of PAHs, their relationship was highly significant (r >0.6) (Fig.…”
Section: Composition Analysismentioning
confidence: 66%
See 2 more Smart Citations